(untitled) (Revista Brasileira de Contabilidade e Gestão, 2016)
The ease in storing images and the high concentration of images in databases drove the generation of applications that involved the consultation, retrieval, and analysis of these images. To extract information from an image base, algorithms are required that can be applied to a large mass of data, while classifying and finding patterns in relationships. To make image mining, as well as multimedia data, possible there is an interdisciplinarity that connects this concept, and everything about it will be covered in this article.